Ritu Haritaki (Seasonal Regimen with Indian Rhubarb) – A Boon to Seasonal Health. - Mahadev Gomare, Janhvi; T.J., Sushma; Warad, Vijayalaxmi; V. Binorkar, Sandeep; L., Lavanya; Kumar K. M., Anil; J. Patil, Sharangouda; Reddy P., Sudhakar (Journal of Neonatal Surgery, 2025)
Haritaki, scientifically known as Terminalia chebula, is a prominent herb used in traditional Ayurvedic medicine. Haritaki is a deciduous tree native to South Asia, with the fruit being the most utilized part in medicinal preparations. It is characterised by its astringent taste and is believed to balance the doshas in body. It possesses five rasas except lavana with Kashaya rasa predominant. Haritaki is renowned for its therapeutic properties including its antioxidant, anti-inflammatory and antimicrobial activities. It is Rasayana (rejuvenator) and best among pathya (wholesome to body). Its Rasayana effect will be achieved by consuming it with different anupanas (vehicle) in different ritus (seasons) known as Ritu haritaki. Haritaki is considered as mother. Like mother takes care of whole family, similarly Haritaki will takes care of body. Intake of haritaki in every ritu along with different anupana is known as Ritu haritaki which promotes digestive health, enhances immunity and acts as detoxifier. In this article a systematic review has been done to gather information from available literature of Ayurveda and contemporary science regarding haritaki and its consumption in every season with different anupana with possible scientific substantiation.